Using social science to reduce violent offending - Dvoskin, Joel A. (Joel Alan) (New York ; Oxford : Oxford University Press, 2011)
Bringing together experts in the fields of social science forensic psychology and criminal justice, this book addresses what truly works in reducing violent offending, promoting an approach to correctional policy grounded in an evidence-based and nuanced understanding of human behaviour.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Violent crimes -- United States; Violent offenders -- Rehabilitation -- United States; Crime prevention -- United States; Crime -- Sociological aspects